University of the future: reshaping Malaysian universities relevance through humanising education and 4IR - Brahim, Abdesselam; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2018)
The purpose of this paper is to examine the literature on factors that influence and reshape the future Business Model of universities. It evaluated alternative business model and value proposition for Malaysian Universities of the Future (UotF). This paper adopted the design and system thinking approach. Different customer segments of University have been interviewed. The strategy canvas has been used with business modelling tools such as Business Model Canvas (BMC) and Value Proposition Design Canvas (VPC), these are the modelling tools, they were used to design and evaluate alternative business model and value proposition. It has supposed that the University of the future is linked to a range of business to ensure its sustainability, and to have multiple sources of funding. Therefore, it is recommended to offer a variety of values such as Learning/ Researching/Improve served in several channels, mostly linked to the digital world, and forms balanced future leaders. In our opinion, these generic prototype options will help university decision makers, planners, and relevant stakeholders to continuously enhance and customize the sustainable, agile, and competitive business models.